2020
DOI: 10.1007/s13760-020-01407-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social media use on depression in multiple sclerosis patients

Abstract: Social media is a powerful tool in providing information and support for minority groups such as patients with chronic diseases. We aimed to assess the link between using online social media and depression in a sample population of Iranian Multiple Sclerosis (MS) patients. In this cross-sectional study, a number of MS patients between 18-55 years were recruited. The Persian-language version of the Beck Depression Inventory-II (BDI-II-Persian) was used to screen MS patients for depression. We selected a cutoff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Significant difference in QOL was also found between patients who were concerned with the most prevalent issue and those who were not for the NT and RS patients, but not the CT patients (Additional Table 2). It is not surprising that NT and RS patients' QOL is more significantly affected as these are vulnerable times in the survivorship trajectory and the psychological distress confronting them is well reported in the literature [4,53,54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant difference in QOL was also found between patients who were concerned with the most prevalent issue and those who were not for the NT and RS patients, but not the CT patients (Additional Table 2). It is not surprising that NT and RS patients' QOL is more significantly affected as these are vulnerable times in the survivorship trajectory and the psychological distress confronting them is well reported in the literature [4,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer survivors experience high level of physical, emotional, and social problems related to their cancer and treatment [3][4][5][6][7]. Besides the short-term adverse effects of cancer treatment, cancer treatment can also cause long-term (late) health effects.…”
Section: Introductionmentioning
confidence: 99%
“…This study also found significant difference in QOL between patients who were concerned with the most prevalent issue and those who were not for the newly diagnosed and recurrence patients, but not within those who had completed treatment. It is not surprising that newly diagnosed and recurrence patients' QOL is more significantly affected as these are vulnerable times in the survivorship trajectory and the psychological distress confronting them is well reported in the literature [4,[63][64][65]. This finding also underscores the importance of creating an environment that assesses, monitors and supports the information and supportive care needs for these at risk patients.This is critical as well informed and supported patients have been associated with many positive outcomes, including, increased patient involvement in decision making, increased satisfaction with treatment decisions, enhanced coping during the diagnostic, treatment and post treatment phases of illness, decreased anxiety and mood disturbances, and less emotional distress [18,19,23,[66][67][68].…”
Section: Discussionmentioning
confidence: 91%
“…The biomedical definition of cancer survival refers to population of cancer patients who live disease-free for at least 5 years after treatment. In contrast, the National Cancer survivors experience high level of physical, emotional, and social problems related to their cancer and treatment [3][4][5][6][7]. Besides the short-term adverse effects of cancer treatment, cancer treatment can also cause long-term (late) health effects.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of cancer stresses any individual; this is related to the symptoms of the disease and to the psychology of its affliction 1 2. To many people, cancer implies a death sentence; to others it implies suffering and pain 3 4.…”
Section: Introductionmentioning
confidence: 99%